Kajian Eksperimental Penggunaan Limbah Biji Karet Sebagai Pengganti Agregat Kasar Pada Campuran Beton Ringan Kombinasi Pasir Tanjung Raja dan Sikament-LN - opink lindy alresta (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
The using of material substance that utilized waste stuff is getting enough attention nowadays. Rubber seed was the one of waste stuff that used in this study as a substitution of coarse aggregate. The aim of this study is to knowing the characteristic of rubber seed’s lightweight concrete which is involved the heavy volume and compressive strength. Overall, this study was done in Civil Engineering department of Sriwijaya University. The concrete specimen was made into 63 sample which is involved 27 of them were rubber seed’s lightweight concrete, the other 27 of them were rubber seed’s concrete + sikament –LN, and the other 9 of them were normal concrete using sifter coral. The specimen was made as cuboid in 15x15x15cm dimensions and 6 pieces of mortar samples. This study used superplasticizer material as Sikament-LN which is expected to increase load’s compressive strength, whereas the sifter coral’s concrete was made as a compare to rubber seed’s compressive strength and also the rubber seed’s heavy volume. Through this study was obtained the lightweight concrete value which is involving the heavy volume value and the compressive strength value in 28 days for 25% was obtained 1818,57 kg/m3 and 12,59 Mpa. For 50% was obtained 1680,00 kg/m3 and 6,63 Mpa, for 75% was obtained 1530,07 kg/m3 and 6,89 Mpa. Whereas to rubber seed’s concrete + Sikament-LN was obtained the heavy volume and the compressive strength for 25% is 1839,51 kg/m3 and 14,15 Mpa, for 50% was obtained 1706,67 kg/m3 and 10,96 kg/m3, for 75% was obtained 1533,83 kg/m3 and 8,52 Mpa. Keywords : Rubber seed, Lighweight concrete, Sikament-LN, Compressive strength